2021
DOI: 10.1108/jacpr-12-2020-0566
|View full text |Cite
|
Sign up to set email alerts
|

Do economic, social and political globalization affect terrorism? Fresh evidence from international panel data

Abstract: Purpose This paper aims to investigate the impact of economic, social and political globalizations on the incidents of global terrorism. Design/methodology/approach The authors apply negative binomial regressions model because the variable is event count. The sample size covers 195 countries from 1990 to 2017. Findings There is strong evidence that the higher level of economic and social integrations internationally lead to a reduction in terrorist activities. However, the results relating to political glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Our empirical findings are supported by the prior literature. For instance, Rajput et al (2021) elucidated the globalization-terrorism nexus for developing economies and concluded that economic globalization is inversely connected with terrorism activities. Similarly, Asongu and Biekpe (2018) also provide evidence regarding a negative interconnection between globalization and terrorism for African economies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our empirical findings are supported by the prior literature. For instance, Rajput et al (2021) elucidated the globalization-terrorism nexus for developing economies and concluded that economic globalization is inversely connected with terrorism activities. Similarly, Asongu and Biekpe (2018) also provide evidence regarding a negative interconnection between globalization and terrorism for African economies.…”
Section: Resultsmentioning
confidence: 99%
“…Naseer et al (2021) discussed the case study of a developing economy and elucidated that globalization is one of the leading factors of terrorism. Rajput et al (2021) also illustrated the globalization-terrorism nexus for 195 economies. The empirical analysis revealed that economic globalization exerts a negative influence of terrorism; however, the study could not find the significant correlation between political and social globalization and terrorism.…”
Section: Globalization and Terrorismmentioning
confidence: 99%
See 1 more Smart Citation